Postoperative dysesthesia after PVCR without anterior support applied in Yang's type A severe spinal kyphoscoliosis - Wu, Hangqin; Ding, Jie; Yang, Junlin; Sui, Wenyuan (Frontiers in Surgery, 2023)
Backgrounds: Incidence and characteristics of postoperative dysesthesia (POD) has not been reported for posterior vertebral column resection PVCR in treatment of severe spinal kyphoscoliosis. Objective: To investigate incidence and characteristics of POD in PVCR without anterior support applied in Yang's Type A severe spinal kyphoscoliosis. Material and methods: From August 2010 to December 2019, 167 patients diagnosed with Yang's Type A severe spinal kyphoscoliosis underwent PVCR without anterior support applied were retrospectively reviewed. All the patients were monitored by 5 modes of Intraoperative multimodal neurophysiological monitoring. Neuro-monitoring data, radiographic parameters and neurological complications were reviewed and analyzed. Incidence and characteristics of POD were further summarized. POD was defined as dysesthetic pain or burning dysesthesia which could be caused by spinal cord kinking or dorsal root ganglion (DRG) injury but with no motor deficits.Results: PVCR without anterior support was successfully conducted in all 167 patients. Intraoperative monitoring events occurred in 5 patients. One out of these 5 patients showed postoperative spinal cord injury (Frankel level C), but completely recovered within 9 months post-operation (Frankel level E). The number and osteotomy space of vertebrae resection 3 were 1.28 levels and 3.6 cm, respectively. POD was confirmed in three cases (3/167, 1.8%), who were characterized as kyphosis with the apex vertebrae in T12 with the kyphotic Cobb angle of 100°, 115°and 122°, respectively. The osteotomy space of vertebrae resection in the 3 patients were 3.9cm, 3.8cm and 4.2cm, respectively. After the treatment by drugs administration, all 3 patients presented pain relief with duration from 12 to 36 days. The pain gradually moved to distal end of a proper DRG innervated region near the end.: The incidence of POD was 1.8% (3/167) in Yang's Type A severe spinal kyphoscoliosis patients who underwent PVCR without anterior support applied in current study. Evoked potential monitoring could not detect the occurrence of POD. POD in Yang's Type A severe spinal kyphoscoliosis after PVCR could be ascribed to spinal cord kinking and DRG injury.